Addition of orlistat to conventional treatment in adolescents with severe obesity - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP (SPRINGER, 2004)
To investigate the efficacy and tolerability of orlistat in obese adolescents, a prospective, open-label, randomised, controlled pilot trial was performed. A total of 22 adolescents with exogeneous obesity were started on orlistat ( 120 mg tid) and a daily multivitamin preparation in addition to conventional treatment which included nutritional and lifestyle modi. cation programmes. The control group consisted of 20 obese adolescents who had similar duration of follow-up under conventional treatment alone. Of the 22 patients, 7 dropped out within the 1st month of the trial due to side effects attributable to orlistat. The remaining 15 patients on orlistat were followed for 5 - 15 months ( average duration of treatment 11.7 +/- 3.7 months). The control group was similar in age, sex, and duration of follow-up ( 10.2 +/- 3.7 months, range 6 - 17 months) to the orlistat group. Compared to initial body weight, patients in the orlistat group lost - 6.27 +/- 5.4 kg, whereas those in the control group gained 4.16 +/- 6.45 kg ( P< 0.001) during the study period. Patients in the orlistat group lost - 7.65% +/- 6.5% of their initial body weight, whereas, those of the control group gained 5.7% +/- 8.3% ( P< 0.001). The body mass index decreased in the orlistat group by - 4.09 +/- 2.9 kg/m(2) while it increased by + 0.11 +/- 2.49 kg/m(2) in the control group ( P< 0.001). Mild gastrointestinal complaints ( frequent stools) were experienced by all patients in the orlistat group. Conclusion: Orlistat could be a useful adjunct in the treatment of severe obesity in adolescents; however, gastrointestinal side-effects limit its usefulness in almost one in three adolescents.
Keywords: adolescents; children; obesity; orlistat; Treatment; DEPENDENT DIABETES-MELLITUS; MULTICENTER; CHILDHOOD; FAT